PENGARUH BAURAN PEMASARAN (PRODUK, HARGA, TEMPAT, DAN PROMOSI) TERHADAP KEPUASAN KONSUMEN DI KFC CBD CILEDUG - Hendri (Pasca Sarjana Universitas Satya Negara Indonesia, 2015)
This study aimed to test: the effect of the marketing mix (product, price, place, and promotion) to customer satisfaction at KFC cbd ciledug. Where the independent variable is the product (X1), price (X2), where (X3), and promotion (X4) affect consumer satisfaction (Y) as the dependentvariable. From the results of this study indicate that: regression equation (Y = 0.495 + 0.040 + 0.031 X1 X2 + 0.143+0.339 X3 X4 + e). Based on statistical data analysis, indicators - indicators in this study are valid and variables are reliable. In the classical assumption test, regression models multicoloniarity free, does not occur heterosdastisitas. Individually, the variable that has the most impact is variable promotion with a regression coefficient of 0.339, followed by a variable with a regression coefficient of 0.143, then the product 0,040 and 0,031 price. Hypothesis testing using t test showed that the promotion variable found to significantly affect customer satisfaction dependent. Then through the F test can be seen that the independent variable feasible to test the dependent variable customer satisfaction. Figures adjusted R square of 0.504 indicates that the variable customer satisfaction can be explained by the variable product, price, place,and promotion.